Fluid Flow Rates Regression in Tank Level Control - Puji Rahayu; Khairunisa Betariani; Rachmadi Tutuka; Ari Adrianto; Nurmalasari (Universitas PGRI Madiun, 2025)
The industrial production process is closely related to control systems, including level control. This is often used to ensure that fluid in the tank is available in the appropriate amount at each stage of the process. The process typically uses an automatic control system such as a Proportional Integral Derivative (PID) Controller that can help measure the accuracy of the data obtained. Therefore, this study aims to examine the effect of flow rate on fluid level control in a tank using linear, exponential, and logarithmic regression analyses. In the process, the effect of the automatic control system (PID Controller) on fluid flow rate was evaluated. The materials used were a 4 mm solenoid and a pump speed variation in the range of 30-50%. Data on fluid level increase were obtained at 0 (n = 1), 60.27 (n = 30), and 180 seconds (n = 61) as the lower, middle, and upper limits. The results showed that fluid flow rate significantly affected the process of controlling fluid level in the tank, and is influenced by the speed of the pump used. Based on the regression analysis, the evaluation of the PID Controller was still classified as good, because the deviation observed in the reading flow rate data was very small.